PROSES AKULTURASI ANTAR ETNIS JAWA DAN ETNIS BATAK DI DESA MALASORI KECAMATAN DOLOK MASIHUL KEBUPATEN SERDANG BEDAGAI PROVINSI SUMATRA UTARA - Lisdawani Silalahi; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study has several goals for the researchers themselves and other students. The first conduct this study is the first that is to mengetahiu about the process of acculturation between Javanese and Batak village Malasori Serdang District of Dolok Masihul Bedagai. The second purpose is how the process of acculturation that occurs between Javanese and Batak village Malasori Serdang District of Dolok Masihul Bedagai. Analyzing the data in this research use descriptive research method Kualitatitif. This is a qualitative descriptive analysis seeks to provide a detailed picture obtained by the reality of the fact-faktalapangan and also supported by the primary data and secondary data in order to support the data-data that exist. Qualitative research is presented in the form of descriptions and assisted with the calculation of figures, percentages, and included in the table, then the data is included in the table and the data will be analyzed by descriptive so that in analyzing research problems can be meaningful and can be explained and be able to answer what is permasalahanya. The research was conducted in the village of Malasori In the District h Dolok Masihul Bedagai Serdang. the results of this field study showed that the presence of changes in the form of social, economic and cultural. It is caused by several factors that influence the process of acculturation.Keywords: Acculturation, Javanese, Batak